Analisis Kinerja Keuangan APBDes Saat Pandemi - Birgita Neysa Naomi Efrem Mentari; Imelda Sinaga; Victoria Ari Palma Akadiati (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
APBDes is the village government's yearly financial plan, which cover revenue, expenditures, and finance to support village development initiatives. The purpose of this study was to determine the financial performance of the APBDes in Gumuk Rejo Village in terms of efficiency, effectiveness, and independence during the pandemic. This research method is a quantitative research technique with a descriptive approach was employed with a population of 2,064 participants. The sampling approach employs the Isaac & Michael formula, with a total sample size of 323 participants. The data was gathered via a questionnaire, which was sent to respondents via social media. The index analysis approach was employed in the data analysis technique. According to the findings of this study, the Gumuk Rejo APBDes' financial performance is efficient, quite effective, and has high independence. Efficient occurs because the village government can provide easy access to village financial reports for users and there is a high level of community participation in village deliberations, it is quite effective because the distribution of information acquisition regarding the implementation of village fund programs funded from the APBDes used is still low, and it is highly independent because the village fund budget used is right on target distribution.